MODERN METHODS OF IDENTIFYING THE CAUSATIVE AGENTS OF RESPIRATORY DISEASES IN CHILDREN - Bakhodirov Behruz Shavkat o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The article provides a general understanding of the shortcomings, inconveniences and modern methods of using classic old methods to identify the causative agents of respiratory diseases in children, as well as the advantages of modern diagnostic criteria and methods for identifying the causative agents of diseases.